KAJIAN EKSEKUSI STRATEGI DENGAN MENGGUNAKAN BALANCED SCORECARD: STUDI KASUS DI PERUSAHAAN JASA KONSULTAN MANAJEMEN - Tukiran, Martinus (Industrial and Systems Engineering Assessment Journal (INASEA), 2009)
Having strategy based on strategy formulation results does not guarantee that the strategy will be carried out. Strategies at the corporate level should also be carried out in the departments/work units in that company down to the level of the individual in charge. A method that is capable to clarify strategy from the corporate level down to the individual level. This study aims to review the implementation method build and carried out by a management consulting service company. Research results reveals that the formulated corporate strategy can be cascaded into the level of work units, therefore creating a work unit strategy map. In accordance with the description of responsibilities and job descriptions for every position holder, this work unit strategy map is descended into the individual level into an Individual Scorecard. The Individual Scorecard clearly depicts strategic aims to be achieved and its achievement is measured from fulfillment of targets in each KPI.